«Maschio e femmina li creò» (Gn 1,27). La teoria del gender nel contesto dell’educazione cattolica: tra critica e dialogo possibile - Trębski, Krzysztof (Warszawskie Studia Teologiczne, 2020)
The “gender theory” expresses the idea that gender of each person is built socially and culturally on the basis of differentiated social roles and stereotypes. In this perspective, physical difference, termed sex, is minimized, while the purely cultural element, termed gender, is emphasized to the maximum and held to be primary. The Catholic Church rejects this ideology, affirms that one’s biological sex is part of the divine plan and that every person should acknowledge and accept his or her sexual identity based on the complementarity of the sexes, along with their equal dignity, and their reciprocity at a biological, functional, psychological and social level. While remaining firm in its positions, the Church seeks to embark on the path of dialogue on the issue of gender, especially in education, by promoting research that seeks to deepen the way in which sexual difference between men and women is lived out in a variety of cultures. This dialogue does not in any way contradict the legitimate aspirations of families to freely base the education of their children upon an integral anthropology, capable of harmonizing the human person’s physical, psychic and spiritual identity. The “gender theory” expresses the idea that gender of each person is built socially and culturally on the basis of differentiated social roles and stereotypes. In this perspective, physical difference, termed sex, is minimized, while the purely cultural element, termed gender, is emphasized to the maximum and held to be primary. The Catholic Church rejects this ideology, affirms that one’s biological sex is part of the divine plan and that every person should acknowledge and accept his or her sexual identity based on the complementarity of the sexes, along with their equal dignity, and their reciprocity at a biological, functional, psychological and social level. While remaining firm in its positions, the Church seeks to embark on the path of dialogue on the issue of gender, especially in education, by promoting research that seeks to deepen the way in which sexual difference between men and women is lived out in a variety of cultures. This dialogue does not in any way contradict the legitimate aspirations of families to freely base the education of their children upon an integral anthropology, capable of harmonizing the human person’s physical, psychic and spiritual identity.